Students' Preferences Regarding Scientific Clubs at the Faculty of Economic Sciences of the University of Warmia and Mazury in Olsztyn - Barańska, Weronika; Kubica, Natalia (Olsztyn Economic Journal, 2024)
The purpose of the research was to comprehensively discuss the areas of scientific interest of students in the various majors at the Faculty of Economic Sciences at UWM in Olsztyn and to identify what activities they find most useful. The research was conducted by a diagnostic survey method using a questionnaire sheet. The survey shows that the scientific clubs at the Faculty of Economic Sciences correspond to the interests of students. Moreover, students indicated that the benefits and activities offered by the clubs are attractive and in line with their expectations. The activities provided by these organizations enable them to develop and achieve the goals they set while participating in the study clubs. The results of the study may contribute to the preparation of a better offer of scientific clubs at the Faculty of Economic Sciences at UWM in Olsztyn so that it is attractive and meets the needs of students of different majors as well as possible.